2023
DOI: 10.25077/jsfk.9.sup.168-174.2022
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Study on Anti-inflammatory Effect of Bioactive Compounds of Velvet Bean (Mucuna pruriens) Leaves Against NF-kB Activation Pathway

Abstract: Activation of nuclear factor-kB (NF-ĸB) receptors potently enhances pro-inflammatory cytokines production thereby promoting inflammatory reactions. NF-ĸB receptor inhibition is one of the targets in overcoming inflammatory reactions. One of the natural ingredients that have the potential as an anti-inflammatory is velvet bean leaf extract (Mucuna pruriens L. (DC.)) which is used by the local people of West Sumatra. This study aimed to investigate the anti-inflammatory mechanism of the bioactive compounds detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…26 The bond affinity value represents the quantitative measure of the bond strength formed between a ligand, referring to a specific chemical composition, and a receptor, which indicated a protein. According to a previous study, 27 a lower bond affinity value showed a more significant and stable interaction between the ligand and the receptor. The bonding affinity quantifies the energy liberated when a bonding molecule engages in an interaction and establishes a bond with the recipient.…”
Section: Resultsmentioning
confidence: 77%
“…26 The bond affinity value represents the quantitative measure of the bond strength formed between a ligand, referring to a specific chemical composition, and a receptor, which indicated a protein. According to a previous study, 27 a lower bond affinity value showed a more significant and stable interaction between the ligand and the receptor. The bonding affinity quantifies the energy liberated when a bonding molecule engages in an interaction and establishes a bond with the recipient.…”
Section: Resultsmentioning
confidence: 77%
“…Previous reports demonstrated that the velvet bean seed extract was effective in decreasing various proinflammatory cytokines including nitric oxide (NO), interleukin 1β, IL-6, and tumor necrosis factor α (TNF-α) to counteract inflammation [20,21]. Moreover, our previous in silico simulation using molecular docking also suggested that several bioactive compounds detected in velvet bean leaf ethanolic extract (particularly geraniol, octadecanoic acid, benzyl acetate, artemin, and zedoarondiol) were capable of acting as potent NF-kB antagonists thereby preventing inflammatory response [22]. However, our present data could not provide the actual inhibitory actions of bioactive compounds in velvet bean leaf extract against NF-kB expression and proinflammatory cytokine release.…”
Section: Discussionmentioning
confidence: 95%